2001
DOI: 10.1200/jco.2001.19.2.305
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Preoperative Chemoradiation Versus Surgery Alone in Patients With Locoregional Esophageal Carcinoma

Abstract: This randomized trial of preoperative chemoradiation versus surgery alone for patients with potentially resectable esophageal carcinoma did not demonstrate a statistically significant survival difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
670
8
40

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,182 publications
(748 citation statements)
references
References 16 publications
30
670
8
40
Order By: Relevance
“…Twelve patients (median age 64 years; 67% male, 58% moderately differentiated, 83% esophageal, 100% HER2‐positive) received a median of 5.6 weeks of treatment (range: 1.1–8.4). Four patients underwent tumor resection and one of the four patients (25%) had a pCR, which was similar to the pCR rates of previously reported studies [1], [2], [3]. However, the number of patients evaluated in the present study was too low to make an accurate comparison with other studies.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Twelve patients (median age 64 years; 67% male, 58% moderately differentiated, 83% esophageal, 100% HER2‐positive) received a median of 5.6 weeks of treatment (range: 1.1–8.4). Four patients underwent tumor resection and one of the four patients (25%) had a pCR, which was similar to the pCR rates of previously reported studies [1], [2], [3]. However, the number of patients evaluated in the present study was too low to make an accurate comparison with other studies.…”
supporting
confidence: 88%
“…Neoadjuvant chemoradiation therapy for patients with localized esophagogastric cancers has been the subject of much discussion and controversy, with conflicting results compared with surgery alone seen in previous randomized clinical trials [1], [2], [3]. Pathologic complete response (pCR) rates after neoadjuvant chemoradiation therapy are in the 25% range [1], [2], [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] In the subset of patients with tumors of the gastroesophageal junction, CRT delivered postoperatively has also demonstrated a survival benefit. 7 To the best of our knowledge, no randomized controlled trials currently exist that compare the outcomes of the sequencing of CRT in relation to surgery in patients with esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Subset analyses demonstrate that only true complete responders have a durable diseasefree and overall survival benefit. [26][27][28][29] The addition of gene therapy to currently employed modalities of chemotherapy, radiotherapy and surgery attempts to enhance the overall antitumor efficacy and increase the number of complete responders. It has been reported that MUC1 is expressed in as high as 43% of esophageal adenocarcinoma specimens and that a majority of these specimens were poorly differentiated advanced neoplasms.…”
Section: Discussionmentioning
confidence: 99%